Solid Phase Extraction-Spectrophotometric Determination Of Isoxsuprine Hydrochloride In Different Samples Using Modified Magnetic Nanoparticales (Journal of Pharmaceutical Negative Results, 2022)
A green, simple and sensitive spectrophotometric method was proposed for the determination of isoxsuprine hydrochloride (ISX), based on the preconcentration with cetyltrimethylammonium bromide (CTAB) modified magnetic iron oxide nanoparticales (MNPs). ISX was coupled with diazotized metoclopramide drug via diazotization-coupling reaction in alkaline medium to form yellow-orange color product which was extracted and measured spectrophotometrically at λmax444 nm. Various parameters affecting the azo-dye removal by adsorption on modified magnetic nanoparticales (Fe3O4@CTAB) such as pH of solution, volume of diazotized reagent, volume of surfactant, amount of adsorbent and type of desorbing solvent were studied. The linear calibration graph were obtained in the concentration range of 0.3-7.0 µg/mL of ISX, the limit of detection and the limit of quantification calculated to be 0.29and 0.99µg/mL, respectively. Accuracy and precision described by relative standard deviation and relative recovery percentages. The results obtained show that the CTAB-coated MNPs could be employed in the extraction of the drug in the azo dye form from different samples. The ISX was extracted successfully in pharmaceutical forms and spiked samples of river water.